Pengaruh Beberapa Konsentrasi Buah Mengkudu (Morinda citrifolia L) terhadap Pertumbuhan Bakteri Salmonella sp, Escherichia coli secara In Vitro - Teguh Budiharjo; Widodo Widodo; Djoko Priyatno (Poltekkes Kemenkes Semarang, 2015)
This study aims to determine the inhibition of Morinda citrifolia to the growth of Escherichia coli and Salmonella sp through in vitro. This study used a bacterial isolate of E. coli and Salmonella sp gotten from Health Laboratory of Central Java. The design of research uses completely randomized design with six treatments which the concentration of 0% as control. Results of Mengkudu juice is produced from 500 grams of ripe Morinda citrifolia, crushed and then squeezed. With different concentration used were, 20%, 40%, 60%, 80% and 100%. All data were analyzed with five treatments using one way anova. Results showed that Morinda citrifolia juice can significantly inhibit the growth of bacteria E. coli and Saalmonella sp (p less than 0.01). The mean inhibition zone formed occurs in 40% concentration of 2.50 mm and then increases by the increasing concentration of Morinda citrifolia juice. Inhibition of growth of Salmonella sp bacteria occurs at 40% concentration which is equal to 1.25 mm and the largest occurs at 100% concentration of 4.33 mm. The test results showed significant difference inhibition in the growth of different Morinda citrifolia juice. The tendency is the higher concentration of Morinda citrifolia juice, the greater inhibition of the growth of E coli and Salmonella sp bacteria. Morinda citrifolia inhibits the growth of E. coli bacteria greater than the Salmonella sp bacteria.